Relationships between the motivational climate created by coaches and athlete engagement in youth sport - Curran, T.; Hill, A. P.; Hall, H. K.; Jowett, G. E. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Within youth sport, understanding how coach behaviours affect the engagement of their athletes is important given high attrition in adolescence. Based on theoretical and empirical accounts of the motivation underpinning athlete engagement, we reasoned that different dimensions of the motivational climate (viz. mastery and performance structures) would be associated with the dimensions of athlete engagement (viz. confidence, dedication, enthusiasm and vigor). Two-hundred and sixty (M age = 13.53 years, s = 1.27) youth soccer players completed measures of athlete engagement and the motivational climate. Multiple regressions indicated that all dimensions of athlete engagement were positively predicted by perceptions of a mastery climate. Unexpectedly, the cognitive aspects of athlete engagement (viz. confidence and dedication) were also positively predicted by perceptions of a performance climate. Canonical correlation analyses further indicated that a linear composite of athlete engagement was associated with higher perceptions of a mastery climate (but not higher perceptions of a performance climate). The findings suggest that the motivational climate matters for athlete engagement in youth sport. Whereas a performance climate may only contribute to cognitive engagement, a mastery climate appears to elicit increases in all dimensions of engagement.